Zygmunt Bauman and the Return of the Gods [Zygmunt Bauman y el Retorno de Los Dioses*] - Retamal-Hernandez, C (Universitat Oberta de Catalunya, 2018)
In the present text, we address the developments that Zygmunt Bauman formulated on modern genocide, linking them with his latest publications on liquid modernity. To do this (1) we explore the validity of the central hypotheses of Modernity and Holocaust and place them in our context. Bauman believes that the Holocaust is the archetype of modern genocides, which has as one of its necessary conditions the production of moral distance. We analyze the meaning of proximity and the “face of the other” as a source of presocietal moral relations. (2) Following the previous ones, we study the problems that imply the “face of the other” in the context of liquid modernity, especially those related to the challenges of fundamentalisms. (3) We then approach the phenomenon of the “religionization of politics” as a confrontation to the secularism of liquid modernity, its impact on our understanding of freedom and security. (4) Finally, we analyze, linking the reflections of Bauman to those of Horkheimer and Adorno, how the center of the “religionization of politics” is constituted by the “sacred fear” of death and the denial of contingency. © Christian Alejandro Retamal Hernández and FUOC, 2018.